Seismic fragility and post-earthquake reparability of circular reinforced concrete bridge columns with low-bond high-strength reinforcements. (December 2021) - Wang, J.H.; Sun, Y.P.; Takeuchi, T.
Abstract: Authors proposed to use low-bond high-strength reinforcement (LBHSR) as the longitudinal reinforcement of reinforced concrete (RC) columns to develop the self-centering RC engineering structures based on the experimental conclusions that the LBHSR minimized residual deformation of test columns because of the low-bond high-strength property. Because the structural form of the proposed RC column was simple and the technology was low-cost, author proposed to use this type of RC column to fabricate the bridge column system. Two bridge archetypes with single and double columns reinforced by LBHSRs and high-bond normal-strength reinforcements (HBNSRs) were designed for numerical analysis using OpenSees program. A modified Young's modulus of steel rebar was used to simulate the steel-bond slip behavior of the proposed RC column with LBHSRs, and the comparison results proved the applicability of this method. Based on the proposed OpenSees element model, seismic fragility and post-earthquake reparability of the designed bridge archetypes with LBHSRs and HBNSRs were compared based on the incremental dynamic analysis results. It was found that the use of LBHSR could greatly improve the post-earthquake reparability and reduce the collapse probability of bridge archetypes. The equations of the FEMA and JRA codes (FEMA, 2009; Tarfan et al., 2019) were used to predict the residual lateral drifts of bridge archetypes, and the comparison results indicated that both codes much overestimated the residual lateral drifts.